Developing Online Assessment Instrument by Using Proprofs Website for Assessing English Reading Competence - Virdania, Serly; Afidah, Nurul; Nur, Luluk Choirun Nisak; Ma'arif, Iin Baroroh; Francisca, Dilla (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
This study is intended to develop assessment instrument by using Proprofs website for the evaluation of learning for first grade students of SMK Kreatif Hasbullah Jombang. This research uses Research and development (R&D) research methods and adapts ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The results obtained from this development research are as follows: (1) The result of media validation is 4,1 (fair category), 2) The result of material validation is 4,5 (fair category). Based on the results, researcher concluded that Proprofs is deserved to be applied after going through a revision process to evaluate learning at SMK Kreatif Hasbullah, especially in evaluating the reading ability of English language learning.